Sudden death due to silent cerebral arteriovenous malformations: case report - Sherin Zain Elabedin; Mohammed Hassan Gaballah; Mohamed Habiballah; Younis Albalooshi; Reham Eissa (Egyptian Journal of Forensic Sciences)
Abstract Background Cerebral arteriovenous malformations (AVMs) are abnormalities of the intracranial vessels that constitute a connection between the arterial and venous systems and lack an intervening capillary bed. Most people with AVMs have no initial symptoms or problems. Hemorrhagic presentation of AVMs is associated with significant morbidity and mortality. Sometimes, AVMs are only diagnosed after death, during an autopsy. Case presentation. A case of a 60-year-old male who was found dead in his tiny room in a shared apartment with no signs of violence around. External examination showed patterned contused abrasions at the forehead. An autopsy revealed the presence of a localized intracerebral hemorrhagic area in the middle of the left hemisphere of the brain with intact skull bones and meninges. Microscopic examinations with hematoxylin–eosin staining were carried out for body organs and the brain; it was possible to identify arteriovenous malformation surrounded by hemorrhage and gliosis. In the present article, we report a rare case of sudden death by a rupture from AVMs that were not demonstrated during macroscopic examination but only after histological examination. Conclusion Pathologists must consider AVMs as a rare cause of sudden death when performing the autopsy.